2018
DOI: 10.1186/s12885-018-5101-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival with nab-paclitaxel plus gemcitabine in metastatic pancreatic cancer in real-life practice: the ANICE-PaC study

Abstract: BackgroundTreatment with nab-paclitaxel plus gemcitabine increases survival in patients with metastatic pancreatic cancer. However, the assessment of treatment efficacy and safety in non-selected patients in a real-life setting may provide useful information to support decision-making processes in routine practice.MethodsRetrospective, multicenter study including patients with metastatic pancreatic cancer, who started first-line treatment with nab-paclitaxel plus gemcitabine between December 2013 and June 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…In this regard, a recently published study confirmed the role of PS, NLR and CA19.9 in a prognostic nomogram developed from a retrospective series of 210 patients treated with first-line Gem-Nab. 28 When planning the study design, we decided to build an instrument specifically addressing the risk of early death instead of general OS. This decision was taken in light of the risks of toxicity associated with FOLFIRINOX and other potential issues impacting on patient daily life, such as the need to implant a central venous catheter for prolonged infusions.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recently published study confirmed the role of PS, NLR and CA19.9 in a prognostic nomogram developed from a retrospective series of 210 patients treated with first-line Gem-Nab. 28 When planning the study design, we decided to build an instrument specifically addressing the risk of early death instead of general OS. This decision was taken in light of the risks of toxicity associated with FOLFIRINOX and other potential issues impacting on patient daily life, such as the need to implant a central venous catheter for prolonged infusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to date, the standard of care for PDAC is a combined regimen with gemcitabine and nab-paclitaxel or FOLFIRINOX. In the ANICE Pac study, the authors retrospectively investigated prognostic factors in patients treated with gemcitabine plus nab-paclitaxel in real life and found normal baseline level of CA19-9 to be an independent prognostic marker for better survival [81].…”
Section: Ca19-9mentioning
confidence: 99%
“…We anticipate that a simple predictive model for OS in unresectable PaC patients will be useful in our daily clinical practice. However, to the best of our knowledge, there have been few reports regarding predictive models in unresectable PaC patients undergoing systemic chemotherapy, although numerous predictive models in PaC patients undergoing surgery has been reported [16][17][18][19][20][21][22][23][24][25]. The goal of the current study is to construct a simple predictive model for OS in unresectable PaC patients treated with systemic chemotherapy and to confirm its accuracy in an independent cohort.…”
Section: Introductionmentioning
confidence: 92%